Estudo químico de Annona coriacea Mart. E Xylopia aromatica (Lam.) Mart. (Annonaceae) - (:unkn) unknown (Universidade Federal de Goiás, 2015)
CHAPTER 01: CHEMICAL STUDY OF VOLATILE ORGANIC COMPOUNDS Annona coriacea Mart. AND Xylopia aromatica (Lam.) Mart (Annonaceae) - In this research was performed the study of the chemical profile of the volatile organic compounds (VOCs) of flowers and leaves of species Annona coriacea and Xylopia aromatica (Annonaceae) by means of extraction in vivo and in vitro, through the techniques headspace-solid phase microextraction (HS-SPME), hydrodistillation and characterization by gas chromatography-mass spectrometry (GC-MS). By the analysis of the volatile fraction of flowers and leaves of A. coriacea it was observed different VOCs, according to the coatings utilized, since the selection of the fiber becomes one of the main factors for VOCs analysis in different vegetables parts. The chemical profile of the flowers of X. aromatica was obtained through HS-SPME, which compared the efficiency of in vivo and in vitro extractions, due to the higher number of VOCs present in the floral aroma. Once were obtained various chemical data, the multivariate analysis of the data was performed, which provided relevant information, contributing to the optimization of some conditions, such as selection of fiber, extraction time and extraction temperature yielded the characterization of the most number of VOCs. In this context, the conditions that presented the most promising results were: fibers CAR/PDMS and PA, extraction time equal the 60 min and extraction temperature of 29 °C. The essential oil of the flowers of X. aromatica was obtained by hydrodistillation and chemically characterized by GC-MS. The major compound present was the pentadecan-2-one (16.38%). The extraction techniques utilized were helpful, however there was qualitative and quantitative variation of VOCs, which is expected due to the extraction process be different. Thus, it is observed that depending on the objective of the survey or that searches for in the volatile fraction, it is necessary to use the technique to give the most promising results for the investigation held or in order to complement each other. In this way, the study of A. coriacea and X. aromatica contributed to the knowledge of the chemical profile of VOCs present in these species, seen from these investigations that the same can be applied in several industrial areas, for example cosmetic, food, among others.
Chemical study of Annona coriacea Mart. and Xylopia aromatica (Lam.) Mart. (Annonaceae)
Keywords: COVs; Annona coriacea; Xylopia aromatica; Flores; Extrações in vivo e in vitro; HS-SPME; Hidrodestilação; Chemometrics; Flowers; Extraction in vivo and in vitro; Hydrodistillation; CIENCIAS EXATAS E DA TERRA::QUIMICA